2007
DOI: 10.1007/s00360-006-0135-2
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic and ionoregulatory responses of the Amazonian cichlid, Astronotus ocellatus, to severe hypoxia

Abstract: We examined the metabolic and ionoregulatory responses of the Amazonian cichlid, Astronotus ocellatus, to 20 h exposure to severe hypoxia (0.37 +/- 0.19 mg O(2)/l; 4.6% air saturation) or 8 h severe hypoxia followed by 12 h recovery in normoxic water. During 20 h exposure to hypoxia, white muscle [ATP] was maintained at normoxic levels primarily through a 20% decrease in [creatine phosphate] (CrP) and an activation of glycolysis yielding lactate accumulation. Muscle lactate accumulation maintained cytoplasmic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
68
5
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(88 citation statements)
references
References 42 publications
11
68
5
2
Order By: Relevance
“…A similar hypoxiainduced decrease in branchial Na + /K + -ATPase activity was recently reported in Amazonian oscar and European flounder (Richards et al, 2007;Lundgreen et al, 2008) and may be reminiscent of a general metabolic suppression strategy in severe hypoxia (Bickler and Buck, 2007). The possible role of NO in decreasing Na The gills of normoxic goldfish had their lamellae embedded in an interlamellar cell mass that disappeared under hypoxia (Fig.4).…”
Section: Respiratory Parameterssupporting
confidence: 77%
“…A similar hypoxiainduced decrease in branchial Na + /K + -ATPase activity was recently reported in Amazonian oscar and European flounder (Richards et al, 2007;Lundgreen et al, 2008) and may be reminiscent of a general metabolic suppression strategy in severe hypoxia (Bickler and Buck, 2007). The possible role of NO in decreasing Na The gills of normoxic goldfish had their lamellae embedded in an interlamellar cell mass that disappeared under hypoxia (Fig.4).…”
Section: Respiratory Parameterssupporting
confidence: 77%
“…The relative short exposure time (24 h) could also be important. Earlier reports of a decreased branchial NKA activity during hypoxia used either stronger hypoxia and/or longer exposures (Richards et al, 2007;Wood et al, 2007;Lundgreen et al, 2008;Hansen and Jensen, 2010). Indeed, shortterm (4 h) hypoxia at a water P O2 of 80 mmHg did not change gill NKA activity in rainbow trout (Iftikar et al, 2010) as we show here for brown trout.…”
Section: Branchial Expression Of Inos and Nnossupporting
confidence: 68%
“…Hypoxia per se can also decrease gill NKA activity in fish (Richards et al, 2007;Wood et al, 2007;Lundgreen et al, 2008;Hansen and Jensen, 2010). It was therefore unexpected that neither nitrite nor hypoxia changed NKA activity in the present experiments (Fig.…”
Section: Branchial Expression Of Inos and Nnosmentioning
confidence: 45%
“…These results, in combination with the absence of lactate accumulation in white muscle, indicate anaerobic metabolism is only beginning to be employed to supplement energy demands at this level of oxygen deprivation, and metabolic depression is an effective way of conserving ATP until A. ocellatus is faced with almost anoxic conditions. In other studies with comparable lengths of hypoxia exposure, levels of lactate increased to a greater extent in plasma [4.9-fold (Richards et al, 2007); 11-16-fold (Wood et al, 2007)] and white muscle [2-3-fold (Richards et al, 2007;Wood et al, 2007)] than in the current study. This discrepancy in lactate accumulation during hypoxic exposure is most likely a result of the quick entry into hypoxia (~1·h) for these two studies as compared to the gradual transition into hypoxia of our study (~5·h).…”
Section: Hypoxia-induced Metabolic Depression Routine Metabolic Ratecontrasting
confidence: 53%
“…Recent studies have begun investigation into the various ATP-consuming processes that contribute to the whole animal metabolic depression. These studies have shown significant reduction in Na + ,K + -ATPase in gill and kidney during hypoxia exposure (Richards et al, 2007) which is accompanied by a reduction of ion exchange at the gills and an overall reduction in metabolic nitrogenous waste production (urea and ammonia) (Wood et al, 2007). The decrease in these ATP consuming processes are not accompanied by changes in concentration of ATP (Richards et al, 2007), indicating that A. ocellatus is able to successfully tolerate extended hypoxia exposure because of the reduction in key ATP-consuming processes.…”
Section: Introductionmentioning
confidence: 79%